Lost worlds [videorecording (DVD)] - Sessions, Ruth; Van Beek, Lucy; Geffen, Anthony; Etkind, Marc; Johnson, Corey (A & E Home Video : Distributed by New Video, 2007)
Ancient cities are now accurately and beautifully rebuilt, using all new research and CGI. Places and events explored include the battle at Stirling Bridge, Romania's real life Dracula, the Biblical Jerusalem, lost city of Atlantis, and more.